2007
DOI: 10.1093/jpepsy/jsm096
|View full text |Cite
|
Sign up to set email alerts
|

Practices and Provisions for Parents Sleeping Overnight with a Hospitalized Child

Abstract: In general, parents are given the opportunity to stay at the bedside overnight, but barriers exist that limit opportunities for sleep during their child's hospitalization, and serve to separate families who have a hospitalized child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 14 publications
0
22
0
1
Order By: Relevance
“…During the last 40 years, in the Nordic countries, but also in other western countries, practice has changed from parents being almost absent to the expectation that the parents be together with the child 24/7 during the entire hospital stay (McLoone, Wakefield, Yoong, & Cohn, ; Strembler et. al., ). The argument is primarily that having a parent together with the child will improve the child's experiences and their ability to cope during the hospitalisation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…During the last 40 years, in the Nordic countries, but also in other western countries, practice has changed from parents being almost absent to the expectation that the parents be together with the child 24/7 during the entire hospital stay (McLoone, Wakefield, Yoong, & Cohn, ; Strembler et. al., ). The argument is primarily that having a parent together with the child will improve the child's experiences and their ability to cope during the hospitalisation.…”
Section: Introductionmentioning
confidence: 97%
“…In the Nordic countries, children have the right to have at least one of their parents with them during a hospital stay (Davies, 2010). Taking the parents into the hospitals during the child's admission has been encouraged both by family interest groups and by professionals over the last decades (Stremler, Wong, & Parshuram, 2008). During the last 40 years, in the Nordic countries, but also in other western countries, practice has changed from parents being almost absent to the expectation that the parents be together with the child 24/7 during the entire hospital stay (McLoone, Wakefield, Yoong, & Cohn, 2013;Strembler et.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses described the hospital space as belonging to nurses, as reflected in their reluctance for parents and family members to interact with the child and nurse at night and their suggestions that parents leave the hospital at night, either due to lack of sleep space or based on the presumption that parents will sleep better elsewhere. Furthermore, as in our previous survey of pediatric hospital administrators (Stremler et al, 2008), nurses revealed that families often are separated at night, particularly in higheracuity settings, calling into question whether family-centered care can truly exist in such a context.…”
Section: Discussionmentioning
confidence: 76%
“…In a third study, hospital administrators described practices and provisions related to sleep in pediatric hospitals in North America. The administrators described limits to parents' ability to stay overnight with their child based on child or unit acuity, and many expected involvement of the parent in the child's care at night if they did stay (Stremler, Wong, & Parshuram, 2008).…”
Section: Evidence To Date On Sleep In Pediatric Acute Carementioning
confidence: 99%
See 1 more Smart Citation